Investment Intentions Among Early-Career Professionals in Dakshina Kannada District in India: A Behavioral Perspective - Raghavendra; Naik, Karthik; Prabhu, Vignesh (International Journal of Advances in Business and Management Research (IJABMR), 2025)
This study investigates the key factors influencing investment intentions among early career professionals in Dakshina Kannada, focusing on attitudes, subjective norms, perceived behavioural control (PBC), self-efficacy, and investment intention. A quantitative survey method was adopted involving 220 participants selected through stratified random sampling across five talukas: Mangaluru, Puttur, Moodabidre, Sullia, and Mulki. The data collected via both offline and Google Forms included variables related to investment behaviour and demographics. Descriptive statistics were used to summarise participants’ profiles, and Smart PLS was employed to test the proposed hypotheses and explore variable relationships, including the mediating role of self-efficacy. The findings reveal that attitudes, subjective norms, and PBC significantly influence investment intentions. Moreover, self-efficacy partially mediates the link between PBC and investment intentions, highlighting the importance of confidence in managing financial decisions. This study underscores the value of financial literacy and personal beliefs in investment capabilities as drivers of investment behaviour. The practical implications suggest that financial education programs should aim to build both knowledge and confidence. Additionally, leveraging social influence and improving access to investment resources can enhance investment engagement. This study offers valuable insights for educators, policymakers, and financial institutions aiming to foster investment among young professionals.